Effectiveness of insole use in rheumatoid feet: a randomized controlled trial. (2nd September 2016) - Moreira, E; Jones, A; Oliveira, HA; Jennings, F; Fernandes, ARC; Natour, J
Abstract : Objectives : To assess the effectiveness of foot orthoses with regard to pain, function, quality of life, and global perceived effect in patients with rheumatoid arthritis (RA). Method : A double-blind randomized controlled trial (RCT) was carried out. Eighty women with RA were randomly assigned to an experimental group (EG) or a control group (CG). The EG used an insole with metatarsal and medial arch supports and the CG used a flat insole for 6 months. Evaluations performed at baseline and after 45, 90, and 180 days by a blinded assessor were: foot pain while walking and at rest, function, quality of life, and global perceived effect with treatment. Results : The groups were homogeneous for all parameters at baseline. A statistically significant improvement (p < 0.001) was found in the EG regarding pain while walking (mean difference: −2.2 for the right foot and −2.1 for the left foot) and at rest (mean difference: −0.3 for the right foot and −0.5 for the left foot) in comparison to CG. There were no differences in any other observed measures. The time of insole use correlated with foot pain and function in the EG. Conclusions : Foot orthoses with metatarsal and medial arch supports decreases pain during walking and at rest in both feet in patients with RA. Time of insole use correlated with improvements in pain and function.